1998
DOI: 10.3354/meps172101
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variability in temperature and the recruitment of Irish Sea cod

Abstract: A short review shows that in cold, arctic regions of the North Atlantic positive relationships are generally observed between cod recruitment and water temperatures whilst negative relationships are observed in warm-temperate regions. According to this relationship, cod recruitment in the Irish Sea should be negat~vely related to sea temperature. Using 3 ~ndependent sources of longterm temperature records we test this hypothesis and show a highly significant connection between the recruitment of cod and temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 7 publications
3
39
0
Order By: Relevance
“…(b) Estimated required median temperatures ("C) to complete development to Stages 4a and 4b during the period of drift as calculated above (1991). In another cold-water species at the so.uthern edge of its distribution, Irish Sea cod, a strong inverse relationship between temperature and recruitment was also found (Planque & Fox 1998). Recently, Lange & Greve (1997) proposed that temperature acts before spawning on gonadal maturation, which-if one supposes that a fish species has a bellshape-like distribution over the temperature rangein their view would also explain the positive relationship with temperature near the cold water limit and the negative relationship near the warm-water limit.…”
Section: Year-class Strengthmentioning
confidence: 80%
See 1 more Smart Citation
“…(b) Estimated required median temperatures ("C) to complete development to Stages 4a and 4b during the period of drift as calculated above (1991). In another cold-water species at the so.uthern edge of its distribution, Irish Sea cod, a strong inverse relationship between temperature and recruitment was also found (Planque & Fox 1998). Recently, Lange & Greve (1997) proposed that temperature acts before spawning on gonadal maturation, which-if one supposes that a fish species has a bellshape-like distribution over the temperature rangein their view would also explain the positive relationship with temperature near the cold water limit and the negative relationship near the warm-water limit.…”
Section: Year-class Strengthmentioning
confidence: 80%
“…Year-to-year variability in temperature has been shown to be linked with year-class strength also in a number of other fish species (Frank 1991, Planque & Fox 1998, but the correlation appears to vary over the range of distribution. Positive relationships occur near the northern (cold water) limits, negative relationships are found near the southern (warm water) limits and no relationship is observed in the centre of the distribution (Frank 1991).…”
Section: Year-class Strengthmentioning
confidence: 99%
“…Several studies have suggested links between sea temperature and recruitment for various marine species (Dickson et al, 1974;Ottersen and Sundby, 1995;Rutherford and Houde, 1995;Henderson and Corps, 1997;Planque and Fox, 1998;Quinn and Deriso, 1999;van der Veer and Witte, 1999;Fox et al, 2000). Considering cod in the North Atlantic, Planque and Frédou (1999) showed that recruitment success was associated with warmer conditions for stocks at the northern edge of the range and with colder conditions for those at the southern edge of their range.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases single factors seem to explain a considerable part of the recruitment variability (e.g. Planque and Fox, 1998), however, in most cases a suite of environmental factors is involved (e.g. Megrey et al, 1995;JarreTeichmann et al, 2000).…”
Section: Prediction Of Recruitment Incorporating Environmental Variabmentioning
confidence: 99%